Peran Kebijakan Dividen Dalam Memediasi Profitabilitas dan Kebijakan Pendanaan Terhadap Nilai Perusahaan - Desire Nur Addin Afeeanti; Indah Yuliana (Faculty of Economic and Business, 2020)
This study examines the role of dividend policy in mediating profitability and leverage on firm value. The method used in this research is Structural Equation Modeling-Partial Least Square (SEM-PLS) to test the relationship between variables. This study uses data on annual report of go-public companies in 2014-2018 period. ROE and ROA are independent variables (X1), DER and DAR are independent variables (X2). While PER and PBV are the dependent variables and DPR and DY are intervening variables. This study resulted in profitability and leverage has positive and significant effect, but the dividend policy negative and no significant effect on firm value. Profitability has positive and significant effect, but leverage has a significant negative effect on dividend policy. Dividend policy has not been able to mediate between profitability and leverage on firm value.